AB0553 Association of Urinary Sodium and Potassium Excretion with Blood Pressure in Patients with Systemic Lupus Erythematosus. (9th June 2015) - Barnado, A.; Oeser, A.; Zhang, Y.; Titze, J.; Stein, C.M.; Chung, C.P.
Abstract : Background: Sodium and potassium intake are modifiable determinants of blood pressure in the general population. Higher sodium and lower potassium urinary excretion, as well as a higher sodium:potassium ratio, are associated with elevated blood pressure. The prevalence of hypertension and cardiovascular disease are increased in systemic lupus erythematosus (SLE), but the contribution of sodium and potassium intake is not known. Objectives: To examine the hypothesis that urinary excretion of sodium and potassium are related to blood pressure in SLE. Methods: We studied 178 patients with SLE and 86 controls frequency-matched for age, sex, and race. First morning urine specimens were collected and urine sodium and potassium concentrations measured by flame photometry. The Kawasaki formula, a validated method that incorporates age, sex, height, weight, and urinary creatinine, was used to estimate 24 hour urine sodium and potassium excretion. Blood pressure was the average of two resting measurements. Fisher's exact and Mann-Whitney U tests were used to compare categorical and continuous variables, respectively. The associations between systolic (SBP) and diastolic blood pressures (DBP) with estimated 24 hour urinary sodium, potassium, and sodium:potassium ratio were tested using Spearman correlation and then modeled using linear regression adjusting for age, sex, and race. Two-sided p values <0.05 were significant. Results: SLE patients and controls had a similar mean age (40.8±12.4 vs. 41.2±12.0, p=0.76), were predominantly female (88% vs. 86%, p=0.70) and Caucasian (68% vs. 72%, p=0.67). Compared to controls, SLE patients had significantly higher rates of hypertension (44% vs. 19%, p<0.001) and significantly higher rates of anti-hypertensive use (36% vs. 12%, p<0.001). SLE patients and controls had a similar mean SBP (120±17 vs. 118±14 mm Hg, p=0.63) and DBP (73±13 vs. 71±10 mm Hg, p=0.21). The estimated 24 hour urinary sodium excretion was similar in SLE patients vs. controls (4.2±1.8 vs. 4.5±2.1 grams, p=0.54), but the estimated 24 hour urinary potassium excretion was significantly lower in SLE patients compared to controls (2.0±0.7 vs. 2.4±0.9 grams, p<0.001). The urinary sodium:potassium ratio was higher in SLE patients than in controls (2.2±0.7 vs. 1.9±0.6, p=0.001), and this difference remained significant when subjects taking anti-hypertensive drugs, including diuretics, were excluded. In SLE patients, higher urinary sodium: potassium ratio was significantly associated with higher SBP [β coefficient (95% CI) =4.01 (0.57-7.46), p=0.023] and DBP [β coefficient=4.41 (1.71-7.11), p=0.002] after adjustment for age, sex, and race. In controls, there was no significant association with estimated 24 hour urinary sodium and potassium values and SBP and DBP with a borderline significant association between higher urinary sodium: potassium ratio and higher DBP [β coefficient=3.68 (-0.07-7.43), p=0.054]. Conclusions: SLE patients had significantly lower estimated 24 hour urinary potassium and higher estimated 24 hour urinary sodium:potassium ratio than control subjects. The estimated 24 hour urinary sodium:potassium ratio was significantly associated with SBP and DBP in SLE patients. Further studies are needed to evaluate the impact of diets with low sodium and high potassium content on blood pressure in SLE patients. Disclosure of Interest: None declared